The Influence of Indonesian Language in Business Social Media Content Strategies - Azka Muharam; Aurelia Widya Astuti; Sayudin Sayudin; Ahmad Bahar Sagita; Muhammad Urfan Ullah (Riviera Publishing, 2024)
Social media has become a vital platform in modern business marketing strategies. This research aims to examine the influence of Indonesian in business social media content strategy and its impact on customer engagement and achieving business goals. We conducted this research using a mixed approach, including social media content analysis, online surveys, and interviews with business professionals. The research results highlight the important role of Indonesians in business social media. Language is the main tool in communicating with customers. Using correct and relevant language in social media content contributes significantly to increasing customer engagement. Posts with language that is clear, easy to understand, and free from language errors get more positive responses, such as likes, comments, and shares, which encourage more active interactions between companies and customers. In addition, this research underlines the importance of understanding local culture and values. Indonesian language that reflects Indonesian culture and social norms can strengthen the emotional bond between companies and customers, create a stronger sense of identity, and reinforce a positive brand image. The research also shows that the use of slang and local expressions can attract a young audience and expand the reach of a business. However, companies must remain careful to stay true to their brand.